2022
DOI: 10.1002/nop2.1385
|View full text |Cite
|
Sign up to set email alerts
|

Influence of family function on social anxiety among Chinese nursing students: The mediating role of alexithymia

Abstract: Aims This study aims to explore the relationship between family function, alexithymia and social anxiety among Chinese nursing students, especially to determine whether alexithymia acts as a mediator between family function and social anxiety among this social group. Design A cross‐sectional study. Methods From January to March 2021, a cross‐sectional study was conducted among 204 Chinese nursing students at a nursing school of a medical univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 91 publications
(92 reference statements)
1
3
0
Order By: Relevance
“…In our sample of Chinese college students, we observed a significant prevalence of alexithymia, reaching 28.72%. This prevalence aligns closely with findings from previous studies conducted in diverse cultural contexts, such as China (31.9% among nursing students) [6], Italy (27.3% among college students) [70], Jordan (24.6% among university students) [71], New York (27.8% for men and 26.8% for women among college-aged students) [72], and Egypt (22% among university students) [73]. Indeed, an increasing number of studies have documented a heightened prevalence of alexithymia in the general population [74] following the COVID-19 pandemic, surpassing the pre-pandemic rate of around 10% [75,76].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our sample of Chinese college students, we observed a significant prevalence of alexithymia, reaching 28.72%. This prevalence aligns closely with findings from previous studies conducted in diverse cultural contexts, such as China (31.9% among nursing students) [6], Italy (27.3% among college students) [70], Jordan (24.6% among university students) [71], New York (27.8% for men and 26.8% for women among college-aged students) [72], and Egypt (22% among university students) [73]. Indeed, an increasing number of studies have documented a heightened prevalence of alexithymia in the general population [74] following the COVID-19 pandemic, surpassing the pre-pandemic rate of around 10% [75,76].…”
Section: Discussionsupporting
confidence: 91%
“…Researches have indicated that alexithymia is associated with a range of conditions, such as eating disorders, depression, schizophrenia, autism, and substance abuse, and it is also commonly observed in the general population [ 5 ]. Studies of alexithymia using a cut-off point from the Toronto Alexithymia Scale (TAS-20) have reported rates ranging from 15.7% to 31.9% in Chinese college students [ 6 , 7 , 8 , 9 ]. Given that different values are attached to emotional awareness and expression in different countries, there might be some variations across different cultures [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collaboration between various stakeholders has the potential to engender a heightened level of discernment in relation to academic pursuits, professional placements, and supplementary engagements, thereby augmenting the holistic triumph of a student (Dewitt et. al., 2023, Chu et. al., 2023.…”
Section: Full Time Teacher Teaching Approach (Fttts)mentioning
confidence: 99%
“…Many researchers believe that psychological, social and biological factors play a role in alexithymia (Obeid et al, 2020 ). Recent studies have focused on alexithymia levels or its effects on other variables (Chu et al, 2022 ; Giulia et al, 2019 ). Empathy is understanding other people's feelings and putting oneself in another person's situation (Bas‐Sarmiento et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%